(untitled) (International Journal of Environmental Sciences, 2025)
Nigella sativa L. of family Ranunculaceae has been used as a treatment for various diseases, in ancient times. The seeds of N. sativa show extensive pharmacological properties, that include immune potentiating, anti-histaminic, anti-diabetic, anti-hypertensive, anti-inflammatory, and anti-bacterial effects. It is efficacious against various varieties of diseases, including Eczema, Jaundice, Conjunctivitis, Diabetes, Dyspepsia, Hypertension, Paralysis, intrinsic Hemorrhage, Anorexia, Cough, Asthma, Bronchitis, Fever, Headache, and Influenza. The seed of Nigella sativa L. contains important fatty acids such Linolenic and Linoleic acid. Other pharmacologically active chemical substances found in it include Phyosterols, Flavonoids, Tocopherols, Nigellone, Carvacrol, Dihydrothymoquinone, and pinene. Thymoquinone, Thymohydroquinone, Dithymoquinone, Thymol, Carvacrol, Nigellimine, Nigellicine, Nigellidine, and Alphahederin are only a few of the many active substances it contains. One of the most active constituents of the Thymoquinone (TQ), is therapeutically effective against wide range of bacteria, parasites, viruses, fungus, and Schistosoma. Though the exact mechanism is un-indentified, the theory is that the anti-inflammatory and anti-oxidative properties could be useful in treating osteoporosis, as both conditions are linked to inflammation and oxidative stress. Neuroprotective, Nephroprotective, Cardioprotective, Gastroprotective, Hepatoprotective and anti-cancer effects are some important pharmacological properties of Nigella sativa. To verify the safety and efficacy of Nigella sativa L. in treating HFMD patients, further randomized controlled clinical trials are required. This paper is a comprehensive review of the pharmacognostic profile and pharmacological activity of Black Seeds. This information will be valuable for healthcare professionals, researchers, and scientists who work with this plant and need to be informed about it.